Analisis Administrasi Pendidikan Sekolah Dalam Meningkatkan Mutu Pendidikan - Maulana, Rizqi; Darmiyanti, Astuti (Peneliti.net, 2024)
School administration is all activities which include control, management and regulation which involves the cooperation of several parties so that the aim of establishing a school to provide education through the teaching and learning process can run well. Educational administration in schools is very important because it is the framework that regulates daily activities, resources and teaching and learning processes. The factors to be analyzed in this context include planning, organizing, leadership, monitoring, and evaluation. Planning is an important initial stage in educational administration, where goals, strategies and action plans are set. Furthermore, organizing involves managing human, physical and financial resources so that educational goals are achieved. Leadership plays a key role in guiding, motivating, and directing school staff towards the established educational vision and goals. In the context of improving the quality of education, analysis of educational administration in schools is the basis for identifying weaknesses, evaluating success, and designing improvements. The implementation of effective strategies in educational administration, such as improving the curriculum, training for teachers, use of technology, and parental participation, can contribute to improving the overall quality of education.